Comparison of the ellipsoid and simplex methods - Laurinavičius, Eligijus; Raškinienė, Danutė (Lietuvos matematikos rinkinys, 1999)
The ellipsoid method is presented. The least squers functional of the basic solution linear constrains is used as ellipsoid. The Klee-Minty linear programming problem is used to compare the ellipsoid and simplex methods.